Integration of Artificial Intelligence in Indonesian Legislation: Towards Participatory and Transparent Smart Law-Makin - Wardana, Dodi Jaya; Setiyawan, Deni (Fakultas Hukum Universitas Islam Indonesia, 2025)
The rapid development of Artificial Intelligence (AI) has opened significant opportunities for reforming Indonesia's legislative system. The urgency of this research stems from the pressing need to enhance the quality, transparency, and public participation in the legislative process, which has long been perceived as slow, bureaucratic, and unresponsive to the rapidly evolving social dynamics. The presence of AI offers innovative solutions to these challenges through the application of analytical technologies, natural language processing, and legislative automation, which are capable of supporting faster and more accurate data-driven decision-making. The objective of this research is to examine the urgency of AI implementation in Indonesia's legislative process and to identify the opportunities and challenges of its integration, particularly concerning aspects of democracy, accountability, legitimacy, and personal data protection — which aims to safeguard individuals' privacy rights and ensure that data collection, storage, use, and deletion are conducted securely, transparently, and in compliance with the law. This study employs a juridical-normative method, incorporating statutory, artificial intelligence, and comparative conceptual approaches, to achieve a comprehensive understanding. The findings suggest that the application of AI has the potential to enhance participation by involving more stakeholders, particularly the public, in decision-making and policy formation processes, thereby making the outcomes more representative, democratic, and responsive to public needs, while also increasing the accuracy of participation. In conclusion, the integration of artificial intelligence into Indonesia's legislative process holds the potential to foster the creation of laws that are more participatory, transparent, and of higher quality — provided clear supporting regulations, guarantees of privacy protection, and the strengthening of institutional capacity within the state accompany it.